2020
DOI: 10.1177/0300985820980704
|View full text |Cite
|
Sign up to set email alerts
|

Canine Gliomatosis Cerebri: Morphologic and Immunohistochemical Characterization Is Supportive of Glial Histogenesis

Abstract: Gliomatosis cerebri (GC) is a glioma subtype with diffuse neuroparenchymal infiltration without architectural distortion. GC was first used in human neuropathology and remained controversial until its elimination from the diagnostic lexicon in 2016. GC is currently defined as a diffuse growth pattern of glioma rather than a distinct entity. In this article, we characterize 24 cases of canine GC and classify these neoplasms as diffuse gliomas. Selected cases of canine GC were reviewed and immunolabeled for olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…As a differential diagnosis, another form of glioma, gliomatosis cerebri (GC), was considered. Cerebral gliomatosis is a rare type of neoplasm that has been described to infiltrate the spinal cord in dogs [ 39 , 40 ], but, differently from our cases, MRI examination showed that cerebral gliomatosis tended to be widespread, with relative conservation of neuronal architecture [ 40 , 41 , 42 , 43 ], predominantly astrocytic, and without neovascularization [ 44 , 45 ]. In the dogs reported in the present paper, the primary lesions were well circumscribed, did not occupy three continuous lobes, were not present in the thalamus, and the area of the caudal fossa was not affected.…”
Section: Discussionmentioning
confidence: 64%
“…As a differential diagnosis, another form of glioma, gliomatosis cerebri (GC), was considered. Cerebral gliomatosis is a rare type of neoplasm that has been described to infiltrate the spinal cord in dogs [ 39 , 40 ], but, differently from our cases, MRI examination showed that cerebral gliomatosis tended to be widespread, with relative conservation of neuronal architecture [ 40 , 41 , 42 , 43 ], predominantly astrocytic, and without neovascularization [ 44 , 45 ]. In the dogs reported in the present paper, the primary lesions were well circumscribed, did not occupy three continuous lobes, were not present in the thalamus, and the area of the caudal fossa was not affected.…”
Section: Discussionmentioning
confidence: 64%
“…9 However, rare subsets of gliomas (referred to as diffusely infiltrating gliomas or gliomatosis cerebri) infiltrate widely into the neuroparenchyma without causing distortion to its overall architecture. 12 Although highly invasive, diffusely infiltrating gliomas are morphologically and immunohistochemically identical to the more commonly diagnosed nodular gliomas. 12 In fact, it is likely that diffusely infiltrating gliomas represent a growth pattern of canine glioma rather than a separate entity (gliomatosis cerebri), as has been the case in human neuropathology.…”
mentioning
confidence: 99%
“…12 Although highly invasive, diffusely infiltrating gliomas are morphologically and immunohistochemically identical to the more commonly diagnosed nodular gliomas. 12 In fact, it is likely that diffusely infiltrating gliomas represent a growth pattern of canine glioma rather than a separate entity (gliomatosis cerebri), as has been the case in human neuropathology. 12,14 Doublecortin (DCX) is a microtubule-associated protein that plays an essential role in neuroblast migration in cerebrocortical development during embryonal life, but its expression has been also detected in subsets of adult subependymal and hippocampal neurons.…”
mentioning
confidence: 99%
See 2 more Smart Citations